(untitled) (Impetus, 2025)
The present review is circumscribed in the reception of ethnomotor skills in the educational field, which offers alternative lines of intervention at the motor, social, cultural and affective levels in the area of Physical Education, since it allows reflective processes that generate identity cohesion and connections in favor of sustainable development. The purpose of the study was to investigate in the academic production the approach of ethnomotor skills in the Physical Education class or in other educational practices. For this purpose, a qualitative approach was used, and an exploratory systematic review in databases such as Scopus, Web of Science and Google Scholar between 2014 and 2024, taking into account the PRISMA statement, and analysis with Atlas.ti v.9 software. Among the main results, it was observed that ethnomotricity allows the encounter with ancestrality, since it involves the construction of corporeality, spirituality, and cultural knowledge transmitted through shared motor stories and the feelings and knowledge associated with them. In conclusion, body practices from an ethno-educational perspective broaden the epistemic panorama of Physical Education, since they contribute to the curricular transformation that makes visible other motor manifestations of cultural meaning for training in the area.